Trade sustainability and aid under liberalization in fragile least developed countries - Amelia U. Santos-Paulino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This study investigates the effect of trade liberalization on export growth, import growth, the trade balance and the current account of the balance of payments in 17 least developed countries (LDCs) over the period 1970 to 2001. The paper also assesses the marginal relation between capital flows (e.g., aid flows) and import growth, and the trade balance and the current account of the balance of payments. The higher import growth contrasts with the more modest export growth following trade liberalization and this has fundamental policy implications, especially for the balance of trade and the balance of payments. However, the financing and sustainability of the trade deficit in the reforming countries will depend not only on the outcome of trade liberalization, but also on other macroeconomic policies, developments in the real exchange rate and the inflows of foreign capital.
Keywords: C23; F13; F14; F32; 330; trade liberalization; aid; balance of payments; dynamic panel data; least developed countries; Außenhandelsliberalisierung; Export; Import; Zahlungsbilanz; Leistungsbilanz; Vierte Welt